Condições de vida e saúde de idosos residentes no município de Águas de Chapecó - SC - Teston, Maristela (2013)
The multidimensional and dynamic definition of "health" does not have well-established concept. This state depends on secondary factors and resources and access to education, food, housing, goods and services of health infrastructure, conditions of life and work, income, lifestyle, environment, leisure and others. The study aimed to examine the health conditions of the elderly population in the city of Águas de Chapecó / SC. The same cross-sectional nature and the population sample consisted of 651 persons of the said municipality. Inclusion criteria were: age less than 60 years; reside for at least three months in the territory of the municipality, owning at the time of interview cognitive conditions to respond to the questionnaire and / or the presence of a family member or caregiver to assist or make the responses. Data collection took place between May and July 2012 by health workers trained by the researcher and used the structured questionnaire Brasilian Old Age Schedule (BOAS), which is multidimensional, validated and adapted to the elderly population. It includes nine sections: general information, physical health, use of medical and dental services, activities of daily living, social resources, economic resources, mental health needs and issues affecting the respondent, the interviewer's assessment. The results were gathered in two scientific productions which are attached to the text. The first entitled Socio-demographic characteristics and self-reported health of elderly aimed to analyze the socio-demographic characteristics and self-reported health of elderly people of Waters Chapecó - SC. To investigate the association between self-rated health and sociodemographic characteristics of the elderly, we used the chi-square test and Fisher's exact test at a significance level of p ≤ 0.05 and confidence interval (CI) of 95% . To cut this study, 775 of the total sample were excluded 13.5% seniors, totaling 651 individuals, 86% of the initial sample. The results showed that the older, the higher the proportion of elderly people who consider their health as poor or very poor, among others. Statistically significant association between self-rated health, gender and age (p <.05). In scientific II developed as a theme: A population based study associated with depressive symptoms in the elderly. The objective was to determine the prevalence and factors associated with depressive symptoms among the elderly. Data were analyzed using Stata v. 10 (STATA, 2007), bivariate analyzes (chi-square test) and multivariate analysis using logistic regression. Considering these results, it was found consistent with other studies involving the same subject in which there is a high prevalence of depression in older people. It is also evidenced that depressive symptoms Most patients were elderly more vulnerable to impaired functional capacity without gainful employment at the time of interview. Points up the need for the establishment of public policies on mental health for the elderly to maintain them in the community as long as possible to preserve the conditions giving maximum autonomy, thereby reducing the demand on services and helping to reduce spending. The results suggest the need to develop more studies that cover the context in question, and that will contribute to the implementation of preventive instead of curative, providing better quality of life for the elderly population